2017
DOI: 10.1126/sciimmunol.aal2192
|View full text |Cite|
|
Sign up to set email alerts
|

Single-cell RNA-seq and computational analysis using temporal mixture modeling resolves T H 1/T FH fate bifurcation in malaria

Abstract: Differentiation of naïve CD4 + T cells into functionally distinct T helper subsets is crucial for the orchestration of immune responses. Due to extensive heterogeneity and multiple overlapping transcriptional programs in differentiating T cell populations, this process has remained a * Correspondence to: st9@sanger.ac.uk, Ashraful.Haque@qimrberghofer.edu.au or stegle@ebi.ac.uk. # denotes equal contribution † denotes equal contribution Author contributions TL and KRJ performed the single-cell RNA-seq experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

41
309
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 266 publications
(362 citation statements)
references
References 61 publications
41
309
0
Order By: Relevance
“…First used in geostatistics 31 , GP models have been applied to test for differential gene expression over time 32 , including the analysis of bifurcation points 26 , and general tests for temporal variability 25,[33][34][35] .…”
Section: Relationship To Prior Workmentioning
confidence: 99%
See 1 more Smart Citation
“…First used in geostatistics 31 , GP models have been applied to test for differential gene expression over time 32 , including the analysis of bifurcation points 26 , and general tests for temporal variability 25,[33][34][35] .…”
Section: Relationship To Prior Workmentioning
confidence: 99%
“…Fig. 8), an application of SpatialDE for which previous methods exist [24][25][26] , but previous methods are likely less computationally efficient than SpatialDE. In principle, SpatialDE can also be applied to 3-dimensional data, e.g., from serial sections of 2-dimensional data, or from in situ sequencing when such technologies mature 11,12 .…”
mentioning
confidence: 99%
“…In fact, more than 50 methods have been proposed for this task making a systematic comparison unfeasible for the scope of this manuscript. For this reason, we compared STREAM with 10 state-of-the-art methods well recognized and commonly used by the single-cell community: Monocle2, scTDA, Wishbone, TSCAN, SLICER, DPT, GPFates, Mpath, SCUBA and PHATE 12,[16][17][18][19][20][21][22][23][24] .…”
Section: Supplementary Note 5: Comparison Of Stream With Existing Metmentioning
confidence: 99%
“…For example, the development and heterogeneity and molecular trajectories of T helper (Th) subsets Th1 and Tfh cells during infection with P. chabaudi chabaudi AS, a rodent-infective strains of malaria, were monitored with a computational modeling strategy (a mixture of Gaussian processes models) with scRNA-seq (Lönnberg et al 2017). Those important findings demonstrated that splenic monocytes/macrophages, dendritic cells, and other myeloid cells could support the Th1 fate by influencing bifurcation during infection.…”
mentioning
confidence: 99%